Job recruitment system - Nur Syafiqa, Yusri (2019)
Every year, over 200,000 students graduate from higher education institution. Shockingly, 1 out of 5 graduates remain unemployed, majority from it is a Degree holders. Nowadays, being a university graduate no longer guarantees a job. As the number of graduates continues to climb each year, students are facing tough competition amongst a shaky economy. This system is developed to help the fresh graduates to find a suitable job even before their graduation and for the employers to post the job advertisements. There are three type of users that can access into the system which are student, company and admin. This Job Recruitment System is for students to register, find jobs, apply for the job, manage their resume, and manage their profile information. While, the company or employer can register, upload job advertisements, manage resume, search the desired students and manage account user. Other than that, the admin will manage the accounts of students and the company. The objective of this system is to analyze and design the current problem of this system by produce Software Requirement Specification (SRS), to develop a prototype system in Job Recruitment System and to validate the proposed prototype system in web based. Rapid Application Development (RAD) is the methodology used to develop this system. RAD consists of four stages. First is requirement planning stage, followed by user design stage, rapid construction stage and lastly is transition stage. After the development of the system, client will be given the user acceptance test (UAT) to ensure that all functions work according to the requirement without any error. The UAT testing ensure the system has achieved the objective and be able to solve the problem that happened before.